Falsafah Piil Pesenggiri Dalam Pendidikan Islam: Kajian Atas Nilai Moralitas dan Pembentukan Karakter - Komaruddin, Komaruddin (Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
This research examines the incorporation of the Piil Pesenggiri philosophy within Islamic education, with a specific emphasis on moral and character development. Piil Pesenggiri, representing the philosophical framework of the Lampung community, includes values such as honesty, honor, responsibility, and solidarity, which contribute to the character development of students in the realm of Islamic education. This study utilizes a literature review approach to analyze the significance of these values in relation to the principles of Islamic education, which seek to develop individuals of noble character. The research findings demonstrate that integrating local values such as Piil Pesenggiri into the Islamic education curriculum enriches character development and improves students' comprehension of cultural identity in accordance with Islamic teachings.